Laser metal deposition materials process-performance studies - Yuvaraj Hitesh Kumar (2018)
In this study, Materials-Process-Performance studies were carried out on the specimens that were fabricated by Laser Metal Deposition (LMD) using three different build strategies namely short unidirectional, long unidirectional and bidirectional strategies. The influence of the build strategy on the material utilization efficiency or the powder efficiency was studied to identify the build orientation that optimizes the material usage. The long unidirectional build strategy had the highest powder efficiency followed by the bidirectional and the short unidirectional build strategies. Process evaluation was done to determine the effectiveness of the closed-loop control in maintaining the homogeneity of the build and to study the variations in the key process parameters within the build. The process evaluation results revealed that a significant degree of homogeneity prevailed within the build in all the three build strategies. Compression testing was performed on the LMD specimens to study the influence of the build strategy on the mechanical performance and behaviour of the LMD specimens. The short unidirectional specimens had the highest compressive strength, yield strength and modulus of elasticity followed by the long unidirectional and bidirectional specimens. The test results were also compared with conventionally manufactured specimens to analyse the differences.